2008
DOI: 10.1002/smll.200800858
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Function of Bismuth Nanocatalysts for the Solution–Liquid–Solid Synthesis of CdSe Nanowires

Abstract: Small Bi nanoparticles prepared upon reduction of Bi‐III compounds catalyze the growth of thick CdSe nanowires (see image). The control of Bi particle and CdSe nanowire growth rate allows adjustment of the dimensions of the nanowires, which is important for the preparation of various types of nanowires in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 30 publications
2
94
1
Order By: Relevance
“…We showed that the Bi nanocatalysts grow into large nanoparticles (40-80 nm) upon heating. [43] Also we were able to show that the growth of the Bi nanoparticles could be slowed down in the presence of Cd and Se precursors upon formation of the CdSe nanowires. [43] In summary, the growth mechanism of CdSe nanowires by the SLS method is even more complex than the kinetic reaction control to form different CdSe nanostructures, due to the additional presence of the catalytic nanodroplets.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We showed that the Bi nanocatalysts grow into large nanoparticles (40-80 nm) upon heating. [43] Also we were able to show that the growth of the Bi nanoparticles could be slowed down in the presence of Cd and Se precursors upon formation of the CdSe nanowires. [43] In summary, the growth mechanism of CdSe nanowires by the SLS method is even more complex than the kinetic reaction control to form different CdSe nanostructures, due to the additional presence of the catalytic nanodroplets.…”
Section: Introductionmentioning
confidence: 66%
“…In our previous study, we developed a simple way to prepare pure Bi nanoparticles (D ¼ 3.3 AE 0.5 nm) by the reduction of Bi[N(SiMe 3 ) 2 ] 3 or BiCl 3 with TOP at room temperature. [43] These nanocatalysts can also be in situ produced by mixing the Bi precursors and TOPSe solution (the Se concentration is 1 or 2 M) without additional TOP. We showed that the Bi nanocatalysts grow into large nanoparticles (40-80 nm) upon heating.…”
Section: Introductionmentioning
confidence: 99%
“…The release of heat could influence the crystallinity of the ultra-small nanoparticles because the melting point of nanoparticles is strongly dependent on particle size. [66] Hence the small Bi2Se3 nanoparticles could form amorphous structure.…”
Section: Resultsmentioning
confidence: 99%
“…They nucleate and take a role as catalyst for the crystal growth of CdSe NWs ( Figure 1(b)). Compared to Bi nanocrystal synthesized by chemical methods, 8,23 the Bi thin film makes reaction system simple due to removing the number of cases originated from Bi precursor.…”
Section: Resultsmentioning
confidence: 99%